Understanding The Challenges Associated with Cooperative Learning: An Empirical Study with Primary School Teachers - Adl-Amini, Katja; Baie-Mosch, Franziska; Decker, Anna Theresia; Seiz, Johanna; Ries, Nora; Kunter, Mareike (Revija za elementarno izobraževanje, 2024)
Cooperative learning includes effective methods for increasing student learning in primary school and heterogeneous classrooms. However, teachers do not use it very frequently. The present interview study investigates on which levels of the educational system primary teachers perceive difficulties associated with these methods to be located, and what kinds of conflicting demands they associate with it. The study provides important insights into how challenges related to cooperative learning may be addressed.
Keywords: cooperative learning, implementation difficulties, interview study, primary school, teachers